The Effect of The Land and Housing Lease Law and The Proposed Revision on The Diverting Use and Supply of Land - Seshimo, Hiroyuki (Urban housing sciences, 1996)
In this paper, we analyze the effects of the present Japanese Land and Housing Lease Law, and its effects after the proposed revision. The bargaining power of the landlord is reduced by the present law, while the bargaining power of the tenant will be reduced by the revision of the law. Thus this law causes the hold-up problem of the landlord and the revision will result in the hold-up problem of the tenant. In our model, we prove that the existing law leads to a lower diverting use of land and a lower supply of housing and land for rental than the socially optimal level. Unlikely usual argument, this lower diverting use of the land occurs even if the negotiation cost is zero, and this is caused by the excess investment of the tenant. On the contrary, a greater diverting use of the land will occur if the law is revised. This problem, however, is less serious than that of the present law because landlord can make commitment to the tenant that they will not exercise their higher bargaining power.